Optimalisasi Penerapan Teknologi Penetasan Pada Usaha Pembibitan Ayam Kampung di Kecamatan Kambu Kota Kendari Provinsi Sulawesi Tenggara - Has, Hamdan; Kusuma, Putu Nara; Napirah, Astriana; Libriani, Restu; Sutopo, Dedem; Kurniawan, Widhi (CV. Literasi Indonesia, 2023)
One of the main problems in kampong chickens breeding is the limited natural hatching by hens, the use of automatic hatching machines can help improve the quality of kampong chicken hatchery output. The community service activities carried out by the Lecturer Team from the UHO Faculty of Animal Husbandry aim to help the kampong chicken breeders in solving the problems faced, one of which is hatching in the kampong chicken breeding business. This activity was carried out at the kampong chicken farm in Kendari City, Southeast Sulawesi, the main programs carried out was training in making automatic hatching machines and assisting in hatching chickens. This activity received high appreciation from kampong chicken breeders in Kendari City and succeeded in increasing their ability in kampong chicken hatchery.